Total Knee Arthroplasty in Patients of Advanced Age: A Look at Outcomes and Complications - Passias, Peter G.; Bono, Olivia J.; Bono, James V. (The Journal of Knee Surgery, 2020)
Total knee arthroplasty (TKA) is one of the most highly successful orthopaedic procedures performed in North America. It is also one of the most common procedures performed, and its incidence continues to increase. Despite this, it is the opinion of many that patients of advanced age groups are not ideal candidates to undergo such procedures secondary to the concern over higher complication rates and poorer functional outcomes. This review article attempts to analyze the current body of literature concerning TKA outcomes and to evaluate some of the issues that are more specific to this population when they undergo TKA. It is our hypothesis that the literature does not support this popular misconception, and that older patients who do not have significant medical comorbidities are good candidates to undergo primary TKA. However, certain cohorts of this population are not ideal candidates to undergo this procedure. Also, certain joint reconstructive procedures, such as simultaneous and staged bilateral TKA, are higher risk procedures in this patient cohort.
Keywords: TKA; age; elderly; outcomes; complications